A Computational Exploration: Docking Analysis of Compounds from Foeniculum vulgare as Potential Aromatase Inhibitors for Endometriosis Candidate Therapy - Suryandari, Dwi Anita; Sari, Puji; Sunaryo, Hadi; Istiadi, Khaerunissa Anbar (UI Scholars Hub, 2023)
Aromatase inhibitors (AI) have controlling symptoms and size of endometriotic implants, making them a promising second-line therapy for endometriosis treatment.pretreatment with letrozole, an AI, combined with leuprolide acetate and resveratrol has been found to improve in vitro fertilization (IVF) outcomes in women mild endometriosis.in this study we screening and analysis of ten phenolic compounds from Foeniculum vulgare using molecular docking with Mcole server.from this results showed that three phenolic trans resveratrol (TR), caempherol coumaril (CC) have low gibbs energy compare with resveratrol (R). The binding modalities of compound TR and compound R were hydrogen-bonding between the hydroxyl and oxygen atom and Thr310 and hydrophobic interactions with Phe187, Ala272, Asp275, Ala189.and compound R exhibited cation-π interactions between Val336 as binding activity from aromatase.aromatase inhibitors and resveratrolfrom fennel lies in the potential of resveratrol to modulate hormonal pathways, including aromatase inhibition.